Utilization of Maggot Meal for Eel Fish Feed (Angguila bicolor bicolor) - Hasan, Otie Dylan Soebhakti; Sutrisno, Sutrisno -; Triyanto, Triyanto - (Jurnal Kelautan dan Perikanan Terapan (JKPT), 2023)
The increase in aquaculture production must be accompanied by effective and efficient feed, thus requiring innovation to obtain the appropriate feed ingredients. This research aims to determine the effect of maggot meal and commercial eel feed on the growth, protein digestibility, and production cost of eel (Anguilla bicolor bicolor) aquaculture. Eels were reared in 15 aquariums measuring 60 × 40 × 40 cm, equipped with water filters, with five treatments and three replications. The treatments consisted of maggot meal + eel feed in the following proportions: A1 (0% + 100%), A2 (25% + 75%), A3 (50% + 50%), A4 (75% + 25%), and A5 (100% + 0%). The feed was given twice a day, morning and afternoon, according to the requirements. Data on growth rate and feed efficiency were collected every two weeks, while protein digestibility and production cost were calculated at the end of the 60-day study period. Treatment A2 showed a daily growth rate of 1.218±0.409%, which approached the growth rate of the commercial feed treatment (A1). Treatment A5 had a growth rate of 0.309±0.218% per day, while treatment A1 had a growth rate of 1.440±0.364%. The best feed conversion ratio (FCR) in each phase was obtained in treatment A1, with a value of 1.862±0.086. The highest FCR was found in treatment A5, with a value of 6.455±1.158 in each phase. The best feed efficiency was observed in treatment A2 at 82.79%, while the lowest digestibility was in treatment A4 at 34.88%. The digestibility of feed in treatment A2 was the highest at 58.42%. According to the research findings, the production cost per kilogram of eel was more cost-effective and required less time in treatment A2, with a feed cost of Rp 105,000/kg. The utilization of a combination of maggot meal and commercial feed shows potential as a feed that can be used to enhance growth rate.